Exploring Communication and Course Format: Conversation Frequency and Duration, Student Motives, and Perceived Teacher Approachability for Out-of-Class Contact - Brooks, Catherine; Young, Stacy (International Review of Research in Open and Distributed Learning, 2016)
This study explored how course instructional format (i.e., online, face-to-face, or hybrid) is related to the frequency and duration of out-of-class communication (OCC) between college instructors and students, to student motives for communicating with teachers, and to perceived teacher approachability for conversation outside of class. Though differences in frequency of and student motives for engaging in OCC were not significant, students enrolled in face-to-face courses reported significantly more ongoing/durative OCC with their instructors compared to students enrolled other course types (i.e., online or hybrid). Students in fully online courses reported instructors to seem less receptive to but also less discouraging of OCC than students in face-to-face or hybrid courses. Overall, this study offers a sense of how students who seek informal interaction with instructors beyond the classroom are faring amid the increased reliance on web-based learning environments in higher education.